(untitled) (Advances in Military Technology, 2023)
The mechanics of underwater supercavitating projectiles are currently being extensively researched. The disadvantage of such projectiles is their movement instability. There is a proposal to use stern planing plates to stabilize projectile’s movement. However, the hydrodynamic characteristics of planing plates are known only for low subsonic speeds. This article describes a load study on a planing plate at subsonic, transonic and supersonic speeds with detached and attached shock waves. The obtained calculation results of normal forces satisfactorily agree with the known theoretical solutions and experimental data and can be used to calculate the motion stabilization of supercavitating underwater projectiles with planing stern plates.